Kodo millet varieties released in India for cultivation - Cheruku, Deepika; Ronanki, Swarna; Amasiddha, B (Indian Farming, 2023)
Kodo millet a small seeded annual cereal grass, is one of the oldest crops cultivated in India. It is one of the hardiest crops among the small millets. In this article information on released varieties of kodo millet from 1977–2012 is collected from the report on compendium on released varieties of small millets prepared by Porject Coordinating unit, All India Coordinating small millets improvements project, GKVK, Bengaluru and also updated with information on recently released varieties up to 2021. The following information will be helpful in selecting the varieties suitable for particular agro-climatic zones.